Physical Activity, Sitting Time, and Mortality From Inflammatory Diseases in Older Adults - Cabanas-Sánchez, Verónica; Guallar-Castillón, Pilar; Higueras-Fresnillo, Sara; García-Esquinas, Esther; Rodríguez-Artalejo, Fernando; Martinez-Gomez, David (Frontiers in Physiology, 2018)
Objective: The aim of this study was to examine the independent and combined associations of physical activity (PA) and sitting time (ST) with long-term mortality attributed to inflammatory causes other than cardiovascular disease (CVD) and cancer in a national cohort of older adults in Spain. Design: Prospective study. Setting and Participants: A cohort of 3,677 individuals (1,626 men) aged ≥60 years was followed-up during 14.3 years. Measures: At baseline, individuals reported PA and ST. The study outcome was death from inflammatory diseases when CVD or cancer mortality was excluded. This outcome was classified into infectious and non-infectious conditions. Analyses were performed with Cox regression and adjusted for PA, ST, and other main confounders (age, sex, educational level, smoking, alcohol consumption, body mass index and chronic conditions). Results: During follow-up, 286 deaths from inflammatory diseases (77 from infectious diseases) were identified. Compared to individuals who defined themselves as inactive/less active, mortality from inflammatory diseases was lower in those who were moderately active (hazard ratio [HR]=0.67, 95% confidence interval [CI]=0.50-0.90) or very active (HR=0.48, 95%CI=0.33-0.68), independently of ST. Also, being seated ≥7 h/d versus <7 h/d was linked to higher mortality (HR=1.38, 95%CI=1.02-1.87). The largest risk of mortality was observed in inactive/less active individuals with ST≥7 h/d (HR=2.29, 95%CI=1.59-3.29) compared to those with moderate/very PA and ST <7h/d. Low PA and high ST were consistently associated with a higher risk of mortality from non-infectious inflammatory causes. Associations of PA and ST with mortality from infectious inflammatory causes showed a similar trend, but most of them did not reach statistical significance. Conclusions: Low PA and high ST were independently associated with higher mortality from inflammatory diseases other than CVD or cancer in older adults. Interventions addressing simultaneously both behaviors could have greater benefits than those focusing on only one of them.